PENGELOLAAN KAWASAN CAGAR BUDAYA SULAA DI KOTA BAU-BAU, SULAWESI TENGGARA - Yadi Mulyadi (WalennaE, 2010)
Cultural resource management is not only focused on archaeological remains, but also includes other cultural remains in an area. Therefore, the management of cultural resources located in one area, it's conducted in the frame of management of the heritage area. The main subject of cultural resource management of heritage area is a space where cultural resources are. This study focuses on the management of Sulaa Heritage Area which is located in the coastal area of Bau-Bau, Sulawesi Tenggara Province. It is located in the coastal beach, making the management of Sulaa Heritage Area can not be released with local management and integrated coastal area. Therefore, the proposed management model is management based on spatial. Objects of research are cultural resources found in the area, including Sulaa heritage sites and other cultural resources such as customs, religious rituals and traditional handicrafts. Heritage site consists of Moko Cave, Ancient Tomb Betoambari and Kasulana Tombi Sipanjonga. Customs include traditional dances and ceremonies which reflect the cycle of human life. Religious rituals consist of Pakandeana Anana Maelu, Sumpuana Uwena Syafara, Gorana Oputa, Mauluduna Hukumu, Haroa Rajabu, and Nisifu Syabani. Traditional handicrafts such as handmade weaving crafts typical Buton. The management of Sidaa Heritage Area integrate cultural resources management and landscape of Sulaa area. Thus, this region is integrating cultural and natural heritage as heritage objects that has significant value to maintain the perspective of preservation concept. The expected impact is not only preserving the cultural and natural resources, but also carrying out sustainable benefit for the local community.Pengelolaan sumber daya budaya tidak hanya berfokus pada peninggalan arkeologis, tetapi juga termasuk peninggalan budaya lainnya di suatu daerah. Karena itu, pengelolaan sumber daya budaya yang berada di satu kawasan, itu dilakukan dalam kerangka pengelolaan kawasan cagar budaya. Subjek utama dari pengelolaan sumber daya budaya kawasan cagar budaya adalah ruang di mana sumber daya budaya berada. Penelitian ini berfokus pada pengelolaan Kawasan Warisan Sulaa yang terletak di kawasan pesisir Bau-Bau, Provinsi Sulawesi Tenggara. Letaknya di pantai, membuat pengelolaan Kawasan Warisan Sulaa tidak bisa dilepaskan dengan pengelolaan lokal dan kawasan pesisir terpadu. Oleh karena itu, model manajemen yang diusulkan adalah manajemen berdasarkan spasial. Objek penelitian adalah sumber daya budaya yang ditemukan di daerah tersebut, termasuk situs warisan Sulaa dan sumber daya budaya lainnya seperti adat, ritual keagamaan, dan kerajinan tangan tradisional. Situs warisan terdiri dari Gua Moko, Makam Kuno Betoambari dan Kasulana Tombi Sipanjonga. Adat istiadat termasuk tarian dan upacara tradisional yang mencerminkan siklus kehidupan manusia. Ritual keagamaan terdiri dari Pakandeana Anana Maelu, Sumpuana Uwena Syafara, Gorana Oputa, Mauluduna Hukumu, Haroa Rajabu, dan Nisifu Syabani. Kerajinan tradisional opsional seperti kerajinan tenun khas Buton. Manajemen Area Warisan Sidaa mengintegrasikan pengelolaan sumber daya budaya dan lansekap wilayah Sulaa. Dengan demikian, kawasan ini mengintegrasikan warisan budaya dan alam sebagai benda cagar budaya yang memiliki nilai signifikan untuk mempertahankan perspektif konsep pelestarian. Dampak yang diharapkan tidak hanya melestarikan sumber daya budaya dan alam, tetapi juga membawa manfaat berkelanjutan bagi masyarakat setempat.